What's That? Communicating Veganism through Absurd Fashion - Hasna Nur Azizah, Syifa'; Adinda, Tri; Fadillasari, Annisa; Pratiwi, Kholin; Zahra Husna Luthfiyah, Eka; Fitriani, Nabila; Ramadhani, Erly (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This research explores the communication dynamics in absurd fashion, focusing on the sender-receiver model through Instagram captions and designs. Findings reveal that absurd fashion predominantly communicates through the sender-receiver model, where designers convey messages or critiques through their creations, and consumers interpret them accordingly. The axis of communication in absurd fashion revolves around issues such as, vegetables, and health, reflecting critiques, awareness campaigns, and shifts towards sustainability. Innovative material use, such as vegetables, fruits, and eco-friendly alternatives, displays the industry's commitment to sustainability and environmental awareness. Absurd fashion is a venue for societal analysis and action, in addition to being a means of self-expression. By embracing absurdity in fashion, designers and customers participate in a conversation that goes beyond aesthetics to address important societal and environmental issues. This research focuses light on fashion's transformational power as a communication medium, emphasizing the significance of understanding the ethical and social ramifications of design decisions in the modern fashion world